Rhetorical Patterns of an Argumentative Essay Written by English Department Students of Universitas PGRI Madiun - Sabella Alif Rantina; Lulus Irawati (English Teaching Journal : A Journal of English Literature, Language and Education, 2025)
The purposes of this study are to describe the rhetorical patterns of argumentative essays written by English Department students of UNIPMA and to describe the reasons of choosing the rhetorical pattern of argumentative essays written by English Department students of UNIPMA. The study used qualitative research. There were two sources of data namely the students of Department of English Education and the students essay composition. The data were collected through analyzing the students essay composition and interviewing the students. The data were analyzed by exhibiting the interactive model of qualitative data analysis. The results show that from 20 argumentative essays written by the students, most students use the Thesis Statement (TS) pattern in writing argumentative essays for academic writing equal to 100%. About 65% or as many as 13 student essays exhibit background information (BI) in their essays. There are 7 essays equal to 35% not exhibiting Background Information (BI). 70% or 14 essays students use reservation (RE) to write essays and for those who don't use reservation there are 30% or 6 essays. A total of 40% or 9 essay students used rational appeal (RA) for essay writing and who did not use RA 60% or 11 essays, 25% or 5 essay students used affective appeal (AA) for essay writing and who did not use AA 75% or 15 essays, 60% or 12 essays students use hesitation to write essays and those who do not use HT 40% or 8 essays, 100% or 20 essays students use conclusion. The result of the analysis of interview are those students who already understand this explain that in writing an essay, they must determine the topic first, then make the main ideas and develop them using rhetorical patterns in a coherent and correct manner. Every student learns and understands differently. Teachers should often train students in writing essays so that all students understand how to write essays using rhetorical patterns.